International Business / Economics, Environment and Strategies - Asheghian Parviz; Ebrahimi Bahman (Harper Collins Publishers, 1990)
Preface, Introduction, The Economic Framework of International Business: Theories and Institutions, International Trade Theories, Theories of Foreign Direct Investment and the Multinational Corporation, National Policies Affecting International Trade, The International Monetary System, The Balance of Payments, The Foreign Echange Market, Environmental Aspects of International Business, Broad Environmental Factors Facing an MNC, The Legal and Political Aspects of International Business, The Sociocultural Context of International Business, Technological Forces and Technology Transfer, Patterns of International Involvement, Operational and Strategic Aspects of International Business, A Framework for Global Strategic Management, Application of Global Strategic Management Process, Human Resource Management and Organizational Structure, International Marketing Management and Strategy, International Financial Management and Strategy, Glossary, Index.
Preface, Introduction, The Economic Framework of International Business: Theories and Institutions, International Trade Theories, Theories of Foreign Direct Investment and the Multinational Corporation, National Policies Affecting International Trade, The International Monetary System, The Balance of Payments, The Foreign Echange Market, Environmental Aspects of International Business, Broad Environmental Factors Facing an MNC, The Legal and Political Aspects of International Business, The Sociocultural Context of International Business, Technological Forces and Technology Transfer, Patterns of International Involvement, Operational and Strategic Aspects of International Business, A Framework for Global Strategic Management, Application of Global Strategic Management Process, Human Resource Management and Organizational Structure, International Marketing Management and Strategy, International Financial Management and Strategy, Glossary, Index.